2018
DOI: 10.1016/j.matchemphys.2018.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different functionalized carbon nanostructures as fillers on the physical properties of biocompatible poly(l-lactic acid) composites

Abstract: Effect of different functionalized carbon nanostructures as fillers on the physical properties of biocompatible poly(L-lactic acid) composites, Materials Chemistry and Physics (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…Electrical percolation was not found to take place in CNH composites, with CNT@PLLA showing a sharp increase in conductivity at a lower CNM concentration with respect to RGO@PLLA. The extent of conductivity after the percolation threshold was also significantly higher for the former as compared to for the latter [52].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Electrical percolation was not found to take place in CNH composites, with CNT@PLLA showing a sharp increase in conductivity at a lower CNM concentration with respect to RGO@PLLA. The extent of conductivity after the percolation threshold was also significantly higher for the former as compared to for the latter [52].…”
Section: Introductionmentioning
confidence: 79%
“…RGO powder (from ACS Material, LLC, Pasadena, CA, USA) had lateral dimensions between 1 and 2 µm, and flakes consisted of few irregularly overlapping layers with many corrugations. Chemical modification and purification of the CNMs was performed through diazonium-based reactions, as previously described [52], yielding p-methoxyphenyl-functionalized derivatives (CNM-PhOMe) with improved dispersibility. CNM@PLLA blend solutions in CHCl 3 were prepared by adding a dispersion of CNM-PhOMe in chloroform obtained via sonication to a chloroform solution of PLLA (6 wt%) under continuous stirring.…”
Section: Nanofiller Feature and Scaffold Preparation And Sterilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously reported that physical properties of composite materials, such as modulus, tensile strength and conductivity, can be dramatically improved by adding fillers into polymers [1][2][3][4][5][6][7]. Aluminium oxide, carbon nanotubes, silica particles, and graphene are the commonly used nanoscale fillers, which can significantly change crystalline morphologies of polymer nanocomposites, thus further leading to the improvements in mechanical properties [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%